Diversidade de leveduras associadas ao solo de biomas de Mata Atântica e Amazônico - Ana Raquel de Oliveira Santos (2022)
Yeasts are an important component of soil microbial community. They play important ecological functions, such as carbon, nitrogen and other nutrients cycling, mineralization of organic matter and solubilization of nutrients as phosphate. They act in the soil structure maintenance through aggregates formation. Yeasts also serve as nutrient source for predators and influence plant growth. Most studies on soil yeast diversity focus on temperate climate regions. In Brazil, few studies have been done to inventory yeast diversity and to determine the ecological role of these microorganisms in soil. The aim of this study was to determine the soil yeast diversity in samples collected at RPPN Santuário do Caraça and Itacoatira city - Amazonas, by using different incubation temperatures and isolation methodologies. In RPPN Santuário do Caraça, 370 yeast isolates, comprising 111 species, were obtained from 90 soil samples collected every two months over an approximate period of one year, in three distinct collection sites (forest soil, field and flooded soil). Yeast isolation was performed using a liquid medium enrichment methodology (Yeast Nitrogen Base – YNB plus 8% glucose), incubated at 10, 25 and 35 °C. In Itacoatiara, two different isolation methodologies were used (direct isolation and enrichment) and also a selective medium for Lipomyces species (Yeast Carbon Base-YCB plus 0.1% of cycloheximide). Temperatures of 10°C, 25°C and 35°C were used for incubation in the enrichment methodology. Through the enrichment method, 401 isolates were obtained from 80 soil samples collected at four different collection points. Through direct isolation (plating soil suspension dilutions in YM medium - glucose1%, peptone0.5%, yeast extract 0.3% and malt extract 0.3%) a total of 150 isolates and 40 different yeast species were obtained. Using a selective medium for Lipomyces species (YCB plus Cycloheximide), 47 were obtained. In both collection sites, for the enrichment methodology, both communities showed high values of species richness and diversity. Ascomycota was the predominant phylum in both locations and the most frequently isolated genera were Apiotrichum, Papiliotrema, Schwanniomyces, Nakaseomyces, Saitozyma and basal species of Saccharomycetaceae. Most of the isolated species were exclusive to the collection sites, the isolation methodology or the isolation temperature. Few species were shared between the collection sites and dissimilarity between the communities was due to species substitution along sites (turnover). Thirty-five possible new species were obtained from samples collected in the RPPN Santuário do Caraça, including Phaffia brasiliana, described from isolates obtained in this work. From Itacoatiara samples, 30 possible new yeast species were obtained, in addition to all Lipomyces species. The results of this work show that soils from RPPN Santuário do Caraça and Itacoatira - AM are high diversity and species richness yeast communities and may be a source of potential new yeast species.